Prevalence of teenage pregnancy and pregnancy outcome at a rural teaching hospital in India - Devi, Okram Sarda; Reddy, Ke Manga; Naga Samyukta, B. Sree Chaitanya; Sadvika, P.; Betha, Kalpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Teenage pregnancy accounts for 11% of births worldwide and 95% of these occur in low middle income countries. Pregnancy and its complications are leading cause of death among these girls. This study was done to know the prevalence and to determine whether teenage mothers are at risk of adverse pregnancy outcome. Methods: A retrospective study was conducted at a tertiary teaching hospital, India between July 2015 to Dec, 2017. All teenage mothers delivered after 28 weeks of gestation were included. Women with Diabetes mellitus, renal disease, thyroid disorders were excluded. Demographic data, maternal complications like anaemia, hypertensive disorders of pregnancy, preterm birth, mode of delivery, low birth weight, NICU admissions, stillbirth and early neonatal death were recorded. Results: In the present study, the prevalence was 7% which is less than that of other studies. Incidence of caesarean-Section in the present study was 31%. Amongst the complications oligohydramnious was found to be significantly associated with teenage pregnancy. NICU admissions were needed for 43% of the cases and 31% were LBW. Conclusions: High NICU admission and high LBW in newborns of teenage mothers were noted in the current study. Hence, there is urgent need to focus on the teenage pregnancy.